Prevalence and determinants of opportunistic infections among HIV-infected adults receiving antiretroviral therapy in Ethiopia: A systematic review and meta-analysis - Woldegeorgis, Beshada Zerfu; Zekarias, Zewdineh; Adem, Bulcha Guye; Obsa, Mohammed Suleiman; Kerbo, Amene Abebe (Frontiers in Medicine, 2023)
Background: Reliable data on the burden of opportunistic infections (OIs) after the initiation of antiretroviral therapy (ART) is critical for planning health services and reducing OI-related morbidity and mortality. Nevertheless, there has been no nationally representative information on the prevalence of OIs in our country. Therefore, we have undertaken this comprehensive systematic review and meta-analysis to estimate the pooled prevalence, and identify factors associated with the development of OIs in Human Immunodeficiency Virus (HIV)-infected adults receiving ART in Ethiopia. Methods: Articles were searched in international electronic databases. A standardized Microsoft Excel spreadsheet and STATA software version 16 were used for data extraction and analysis, respectively. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) checklist was used to write this report. The random-effect meta-analysis model was used to estimate the pooled effect. The statistical heterogeneity of the meta-analysis was checked. Subgroup and sensitivity analyses were also performed. Publication bias was examined in funnel plots and the nonparametric rank correlation test of Begg and the regression-based test of Egger. Association was expressed through a pooled odds ratio (OR) with a 95% Confidence Interval (CI) Results: A total of 12 studies with 6163 study participants were included. The pooled prevalence of OIs was 43.97% (95 % CI (38.59, 49.34). Poor adherence to ART (OR, 5.90 (95% CI (3.05, 11.40), undernutrition (OR, 3.70 (95% CI (2.01, 6.80), CD4 T lymphocyte count <200 cells /µL (OR, 3.23 95% CI (2.06, 5.07), and advanced World Health Organization (WHO) HIV clinical stages (OR, 4.84 (95% CI (1.83, 12.82) were determinants of OIs. Conclusion: The pooled prevalence of OIs among adults taking ART is high. Poor adherence to ART, undernutrition, a CD4 T lymphocyte count <200 cells /µL, and advanced WHO HIV clinical stages were factors associated with the development of OIs